Haplotype-resolved chromosomal-level genome assembly of Prunus mahaleb - Chenlong Fu; Meng Li; Zhuang Zhao; Lixia Yu; Xianrong Wang; Zhuangwei Hou; Zefu Wang (Scientific Data)
Abstract Prunus mahaleb is widely utilized as rootstock for cherries in Central Asia due to its exceptional resistance to environmental stressors. In this study, we generated a haplotype-resolved, chromosome-scale genome assembly for P. mahaleb using PacBio HiFi long reads and Hi-C technology. The resulting assembly comprises two haplotypes with sizes of 272.64 Mb (contig N50 = 26.60 Mb) and 271.76 Mb (contig N50 = 30.26 Mb), respectively. We identified 27,965 protein-coding genes (27,627 functionally annotated) and 27,931 protein-coding genes (27,607 functionally annotated) in the two haplotypes, respectively. Additionally, we annotated 145.64 Mb repetitive elements, 2,263 rRNAs, 430 tRNAs, and 780 other non-coding RNAs in haplotype A, and 144.04 Mb repetitive elements, 1,999 rRNAs, 442 tRNAs, and 734 other non-coding RNAs in haplotype B. Further analysis indicated that these haplotypes diverged approximately 2.67 million years ago. This high-quality genome assembly lays a solid groundwork for future initiatives in molecular breeding and functional genomics research for P. mahaleb.